Taste profiling of Centella Asiatica by a taste sensor - Shafiqul Islam, A.K.M.; Zhari, Ismail; Mohd Noor, Ahmad; Abdul Rahman, Othman; Saravanan, Dharmaraj; Ali Yeon, Md Shakaff (MYU K.K., 2009)
Link to publisher's homepage at http://www.myu-inc.jp/myukk/S&M